Contribution to the knowledge of the Jewel Beetles (Coleoptera: Buprestidae) of the Republic of Macedonia - Sakalian, Vladimir (Macedonian Journal of Ecology and Environment, 2001)
A total number of 51 species and subspecies which belong to 14 genera and 8 subfamilies have been established. Two genera (Paracylindromorphus and Cylindromorphus) and 9 species, marked by asterisk in the text, are new for the Macedonian Buprestidae fauna. New faunistic information for the rest of the buprestids has been established. With the collected new taxa the number of jewel beetles known from the Macedonian territory runs to 104. Zoogeographical analysis is made for all known Macedonian jewel beetles. The great domination of Mediterranean taxa shows the high level of Mediterranean fauna impact of the buprestid community formation in this country.